Social-Psychological Significance of Forming the Culture of a Healthy Lifestyle in The Family - Azamat Ismoilovich Saidov (Researchparks Publishing, 2023)
The article deals with the problems of the psychology of a healthy lifestyle in the family, its formation and possible social and psychological ways to solve these problems. Illuminated, scientific and practical results of research related to healthier lifestyle of the individual.